Demographic Evolution in Romania – Convergence or Peripherisation? - Adriana Veronica Litra (Theoretical and Applied Economics, 2006)

(untitled)
Romania began its demographic transition about one century later than the developed countries. We put the blame of this gap on the delayed economic, social and political development in comparison with the Western Europe. But also, it could not be forgotten the shift from a population forced and subdue by the totalitary regime, to a free people to decide when to have a child or how large should be the family. During transition, Romania has pointed many negative demographic evolutions, as compared with the other european countries. It may be said that the transition in Romania over the period 1990-2004 adjusted the classical pattern of demographic evolution. Not fully felt at this moment, we will probably find ourselves few decades later older, less, deprived of skilled labor force and unbalanced as gender ratio.